Spore Formation and Toxin Production in Clostridium difficile Biofilms - Semenyuk, Ekaterina G.; Laning, Michelle L.; Foley, Jennifer; Johnston, Pehga F.; Knight, Katherine L.; Gerding, Dale N.; Driks, Adam (PLOS ONE, 2014)
The ability to grow as a biofilm can facilitate survival of bacteria in the environment and promote infection. To better characterize biofilm formation in the pathogen Clostridium difficile, we established a colony biofilm culture method for this organism on a polycarbonate filter, and analyzed the matrix and the cells in biofilms from a variety of clinical isolates over several days of biofilm culture. We found that biofilms readily formed in all strains analyzed, and that spores were abundant within about 6 days. We also found that extracellular DNA (eDNA), polysaccharide and protein was readily detected in the matrix of all strains, including the major toxins A and/or B, in toxigenic strains. All the strains we analyzed formed spores. Apart from strains 630 and VPI10463, which sporulated in the biofilm at relatively low frequencies, the frequencies of biofilm sporulation varied between 46 and 65%, suggesting that variations in sporulation levels among strains is unlikely to be a major factor in variation in the severity of disease. Spores in biofilms also had reduced germination efficiency compared to spores obtained by a conventional sporulation protocol. Transmission electron microscopy revealed that in 3 day-old biofilms, the outermost structure of the spore is a lightly staining coat. However, after 6 days, material that resembles cell debris in the matrix surrounds the spore, and darkly staining granules are closely associated with the spores surface. In 14 day-old biofilms, relatively few spores are surrounded by the apparent cell debris, and the surface-associated granules are present at higher density at the coat surface. Finally, we showed that biofilm cells possess 100-fold greater resistance to the antibiotic metronidazole then do cells cultured in liquid media. Taken together, our data suggest that C. difficile cells and spores in biofilms have specialized properties that may facilitate infection.